External microwave applicators for hyperthermia therapy: a review - Singh S.; Singh S.P. (My University, 2025)
The continuous evolution of technology leads to increased application in health care. In recent years various efforts have been made in the treatment of cancer, including hyperthermia, but cancer remains a research subject worldwide. However, microwave hyperthermia has been an active area of research due to its advantages of focused heating of cancerous tissue while minimally affecting normal tissue. External hyperthermia applicators are designed and optimized to non-invasively couple microwave energy to the human body or other biological systems to kill cancerous cells and enhance the efficacy of radiation therapy and chemotherapy. These applicators need to meet various characteristics to make them suitable for the said applications, the most essential of which are applicator size, minimum leakage radiation, focused near field, and deep penetration. Many works are available in the literature for the hyperthermia applicator design, but none explores the large number of external applicators for hyperthermia treatment of cancer. This paper presents an extensive exploration of the development of external applicators (i.e., waveguide and planar) with a detailed investigation of the antenna element performance available for hyperthermia applications. This study attempts to identify the physiological and biological factors that affect the efficacy of efficient hyperthermia applicator design. © The Author(s) 2025.; A comprehensive review of numerous external applicators for hyperthermia cancer treatment, not found in open literature. The extensive study of non-invasive microwave hyperthermia applicators aids in designing more efficient versions. Discussed the physiological and biological aspects that influence the efficacy of hyperthermia applicator design. © The Author(s) 2025.